Biomineralization-mimetic preparation of hybrid membranes with ultra-high loading of pristine metal–organic frameworks grown on silk nanofibers for hazard collection in water. Issue 8 (2nd January 2018) - Li, Zhishang; Zhou, Guanshan; Dai, Huang; Yang, Mingying; Fu, Yingchun; Ying, Yibin; Li, Yanbin
Abstract : The efficient incorporation of porous materials into membranes to prepare hybrid membranes for the development of a separation device for water pollution treatment is described. Abstract : The efficient incorporation of porous materials into membranes to prepare hybrid membranes for the development of a separation device for water pollution treatment has been promising yet challenging. Metal–organic frameworks (MOFs) possess superior adsorbability, but their poor processability hampers the fabrication of devices for applications. Inspired by biomineralization, we propose the preparation of electrospun-silk-nanofiber (ESF)@MOF (ZIF-8 or ZIF-67) hybrid membranes with pristine MOFs densely loaded to efficiently remove pollutants in water. The biomineralization-mimetic in situ growth of MOFs on ESF led to the perfect coverage of MOFs, with loading rates reaching 36% and 34% for ZIF-8 and ZIF-67, respectively, which were among the highest levels among commonly used polymer membranes and reported analogues. The loaded MOFs also retained their porosity, which was comparable with that of pristine MOFs. Dynamic investigations revealed that the superior loading rates and porosities derived from the abundant nucleation sites provided by the ESFs and the biomineralization-based growth. The hybrid membranes achieved removal rates of two kinds of heavy metal ion and organic dye that reached nearly 100%. A filtration device was also constructed with a removal rate that was close to 100% in one round. The proposed biomineralization-mimetic growth of MOFs on biomolecular matrices might create a new way for the preparation of multi-functional MOF-based devices.